Manual repositioning of intra-atrial kidney cancer tumor thrombus: a technique reducing the need for cardiopulmonary bypass - Schneider, Meike; Hadaschik, Boris; Hallscheidt, Peter; Jakobi, Hildegard; Fritz, Markus; Motsch, Johann; Pahernik, Sascha; Hohenfellner, Markus (Urology, 2013)
Objective - To describe a feasible surgical technique for patients with renal cell carcinoma associated with a supradiaphragmatic tumor thrombus that avoids cardiopulmonary bypass procedure. - Materials and Methods - From 2004 to 2009, 4 patients with a right kidney tumor and tumor thrombus above the diaphragm (pT3c) underwent manual repositioning of the tumor thrombus out of the right atrium into the inferior vena cava on the beating heart. These patients were aged 65.8 years and had a body mass index of 25.5 kg/m2. Median tumor size was 10.8 cm, and 3 patients had synchronous metastasis. - Results - Manual repositioning of the tumor thrombus was safe and feasible in all patients. Mean operating time was 561 minutes (range, 302-613 minutes), and no perioperative death occurred. Auxiliary cardiopulmonary bypass procedure was applied in 1 patient to remove a preoperatively diagnosed pulmonary embolus. Three patients subsequently underwent systemic therapy for metastatic disease. Median survival was 16 months (range, 1.7-26 months). - Conclusion - Manual repositioning of a vena cava tumor thrombus without cardiopulmonary bypass is a safe and feasible approach. The risk of tumor thrombembolization seems to be low, and cardiopulmonary bypass can be avoided or at least reduced to a minimum time of intervention.